The Copyright Wars at the Digital Frontier: Which Side Are Art Museums On? - Appel, Sharon E. (Journal of Arts Management, Law & Society)
Discusses the copyright problem facing of art museums in the twenty-first century. Impact of technology to arts; How technology affects copyright laws; Issues surrounding copyright.